2023
DOI: 10.3390/antiox12030545
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Strategies for Relieving Stress in Pet Dogs and Cats

Abstract: A variety of physical, emotional, and mental factors can induce a stress response in pet dogs and cats. During this process, hypothalamus–pituitary–adrenal (HPA) and sympathetic–adrenal medulla (SAM) axes are activated to produce a series of adaptive short-term reactions to the aversive situations. Meanwhile, oxidative stress is induced where there is an imbalance between the production and scavenging of reactive oxygen species (ROS). Oxidative damage is also incorporated in sustained stress response causing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 193 publications
1
10
0
Order By: Relevance
“…In our study, the fecal cortisol levels recorded gradually decreased from day 7 to the end (day 28) as compared to the control group. This favorable decreasing effect of feed on cortisol levels may be due to the antioxidant effect elicited, which is also in line with a study that used a mixture of antioxidants (quercetin, resveratrol, curcumin, and vitamin E) in hyperthyroid cats [65].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our study, the fecal cortisol levels recorded gradually decreased from day 7 to the end (day 28) as compared to the control group. This favorable decreasing effect of feed on cortisol levels may be due to the antioxidant effect elicited, which is also in line with a study that used a mixture of antioxidants (quercetin, resveratrol, curcumin, and vitamin E) in hyperthyroid cats [65].…”
Section: Discussionsupporting
confidence: 87%
“…It was documented that sheltered free-roaming dogs express higher plasma cortisol and fecal cortisol metabolites than domestic pets, also suggesting a direct correlation between plasma cortisol and fecal cortisol [ 64 ]. When pets are exposed to restraint conditions, they experience psychological stress with higher levels of cortisol due to activation of the hypothalamus–pituitary–adrenal and sympathetic–adrenal medullas with prolonged sustained oxidative damage [ 65 ]. In our study, the fecal cortisol levels recorded gradually decreased from day 7 to the end (day 28) as compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have revealed that stress causes weight loss along with poor feed intake [ 51 , 52 , 53 ]. Another study additionally found that stress induces anorexia nervosa and a reduction of appetite and food consumption in dogs, and dogs with positive affective states had a stronger tendency to seek food than dogs with negative affective states [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that CRH can increase the permeability of the intestines and increase levels of ACTH in the circulation when there is neuronal stress. The HPA axis is activated by CRH and ACTH when pathogenic infections arise (Fan et al, 2023). Studies show that those who experience stress or anxiety have dysregulated gut flora, which alters the HPA axis (Rahman et al, 2023).…”
Section: Neuronal Pathways For Gut-brain Axis Interactionsmentioning
confidence: 99%